IMI 2021 reports and digest: reflections on the implications for clinical practice - Wolffsohn, James; Jong, Monica; Smith, Earl L., III; Resnikoff, Serge R.; Jonas, Jost B.; Logan, Nicola S.; Morgan, Ian; Sankaridurg, Padmaja; Ohno-Matsui, Kyoko (Investigative ophthalmology & visual science, 2021)
The International Myopia Institute's (IMI) mission is to advance research, education, and management of myopia to decrease future vision impairment and blindness associated with increasing myopia. Its approach is to bring together scientists, clinicians, policymakers, government members, and educators into the field of myopia to stimulate collaboration and sharing of knowledge. The latest reports are on pathologic myopia, the impact of myopia, risk factors for myopia, accommodation and binocular vision in myopia development and progression, and the prevention of myopia and its progression. Together with the digest updating the 2019 International Myopia Institute white papers using the research published in the last 18 months, these evidence-based consensus white papers help to clarify the imperative for myopia control and the role of environmental modification initiatives, informing an evidence-based clinical approach. This guidance includes who to treat and when to start or stop treatment, and the advantages and limitations of different management approaches.
Gesehen am 13.09.2021